The birth of the “digital turn” in bioethics? - Salloch, Sabine (Bioethics, 2023)
The so-called “empirical turn” in bioethics gave rise to extensive theoretical and methodological debates and has significantly shaped the research landscape from two decades ago until the present day. Attentive observers of the evolution of the bioethical research field now notice a new trend towards the inclusion of data science methods for the treatment of ethical research questions. This new research domain of “digital bioethics” encompasses both studies replacing (or complementing) socio-empirical research on bioethical topics (“empirical digital bioethics”) and argumentative approaches towards normative questions in the healthcare domain (“argumentative digital bioethics”). This article draws on insights taken from the debate on the “empirical turn” for sounding out perspectives for the newly developing field of “digital bioethics.” We particularly discuss the disciplinary boundaries, chances and challenges, and potentially undesirable developments of the research field. The article closes with concrete suggestions on which debates need to be initiated and which measures need to be taken so that the path forward of “digital bioethics” will be a scientific success.